Feasibility of Web-based Digital Arabic Gamification Media for Islamic Junior High School Students - Shiddiq, Jamaluddin; Zubaidi, Ahmad; Nur Kholis, Muhammad; Rokhani, Rokhani (Institut Agama Islam Negeri Curup, 2024)
This research aimed to determine the feasibility of web-based digital Arabic language gamification media from experts and users. Specifically, the research investigated the feasibility analysis of web media with the URL: https://belajararabonline14.wordpress.com/ containing Plotagon, Wordwalls, and Genially apps in learning Arabic at the Junior High School level. Generally, Arabic language instruction remains conventional and lacks interactivity. Consequently, students may experience boredom and reduced motivation to learn. Creating interactive materials using gaming principles could be one approach to solving this issue. This research was a type of quantitative descriptive research. This research involved 37 users and 4 validators. Data collection was carried out by distributing questionnaires to validators and users of this media and was analysed using descriptive statistics. The findings showed that web-based digital Arabic language gamification media received very valid responses from experts and users with details: a score of 4.53 from material experts, a score of 4.41 from media experts, a score of 4.93 from teacher responses, and a score of 4.06 from students. These findings suggest to Arabic teachers the potential benefit of incorporating this media as an auxiliary resource in Junior High School-level Arabic language instruction.